Immunogenicity and safety of a low-dose diphtheria, tetanus and acellular pertussis combination vaccine with either inactivated or oral polio vaccine as a pre-school booster in UK children. - Collins, C; Salt, P; McCarthy, N; Chantler, T; Lane, L; Hemme, F; Diggle, L; Buttery, J; Kitchin, N; Moxon, E; Pollard, A (2004)
This open, randomised controlled trial studied the immunogenicity and reactogenicity of two combined low-dose diphtheria, tetanus and acellular pertussis vaccines (Td5aP-IPV, REPEVAX, Aventis Pasteur MSD; and Td5aP, COVAXIS, Aventis Pasteur MSD + OPV, GlaxoSmithKline) in comparison with a standard dose diphtheria pre-school booster vaccine (DT2aP-IPV, TETRAVAC, Aventis Pasteur MSD) in a population of 3.5-5-year-old children administered concomitantly with measles, mumps and rubella vaccine (M-M-R II, Aventis Pasteur MSD). A linked sub-study aimed to evaluate the immunogenicity and reactogenicity of Td5aP-IPV in a population of younger children, aged 3-3.5 years. This study demonstrated non-inferiority of seroprotection rates for diphtheria and tetanus for the study vaccines and comparable immunogenicity for pertussis and polio components of the vaccines. Reactogenicity was similar for all three vaccines. The study vaccines containing low-dose diphtheria antigen (Td5aP-IPV and Td5aP + OPV) are immunogenic and have acceptable reactogenicity for use as a pre-school booster vaccine administered concomitantly with MMR.